APAKAH PERSEPSI KONSUMEN MENGENAI RISIKO DAN KEPERCAYAAN BERPENGARUH TERHADAP KEPUTUSAN - Hendra Prasetya; Nurul Azizah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
On-line buying and selling transactions are currently growing rapidly so that researchers are interested in examining the determinants of the influence of online purchasing decisions, namely risk perception and trust. This study was conducted to determine the significance of the influence of perceptions of trust and risk partially on the decision to make an on-line purchase for students of the Faculty of Economics and Business (FEB) Universitas Wijaya Kusuma Surabaya. This research is an explanatory research with a quantitative approach, with data collection through questionnaires. The results obtained indicate a negative influence of risk perception on on-line purchasing decisions. In addition, a positive influence appears on trust in online purchasing decisions. The implementations of this research are: (1) online product sellers should: (a) minimize risk perceptions for consumers, among others by providing a guarantee for replacement of product orders that are not in accordance with what consumers ordered and are damaged; (b) increasing consumer confidence, among others by increasing the ability of sellers in the form of knowledge and skills in online buying and selling activities, increasing satisfying services for consumers and having integrity in good behavior to consumers, for example being honest; and (2) consumers before deciding to purchase on-line should first seek information related to this matter.